1995
DOI: 10.2307/4002255
|View full text |Cite
|
Sign up to set email alerts
|

Soil Carbon and Nitrogen of Northern Great Plains Grasslands as Influenced by Long-Term Grazing

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
119
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(129 citation statements)
references
References 17 publications
7
119
1
2
Order By: Relevance
“…High fungal density was observed in soil samples from the pristine habitat where no indication of negative livestock impacts ( Table 1). Frank et al, (1995) [31] reported that soil microorganisms are important in nutrient biogeochemistry (e.g. decomposition, mineralization, absorption and soil stabilization) and therefore greatly influence the nutrient storage in the soil.…”
Section: The Effect Of Livestock Grazing On Soil Fungal Density (Sfd)mentioning
confidence: 99%
“…High fungal density was observed in soil samples from the pristine habitat where no indication of negative livestock impacts ( Table 1). Frank et al, (1995) [31] reported that soil microorganisms are important in nutrient biogeochemistry (e.g. decomposition, mineralization, absorption and soil stabilization) and therefore greatly influence the nutrient storage in the soil.…”
Section: The Effect Of Livestock Grazing On Soil Fungal Density (Sfd)mentioning
confidence: 99%
“…Especially gaseous N losses are related with a large fractionation. Thus, ammonia volatilisation has been found to cause enrichment of remaining soil N in grasslands with 15 N (Frank et al 1995). Nitrous oxide produced during nitrification or denitrification is also depleted in 15 N relative to its substrate (Webster and Hopkins 1996;Yoshida 1988), unless it is further reduced to N 2 , leading to an enrichment of nitrous oxide and depletion of N 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The C storages were expressed in g C m-2 . Because the exclosures were at one location and not replicated, we followed the approach of Frank et al (1995) and considered each of the three plots a replication of summary statistics. Values from all sampling points within each plot were averaged.…”
Section: Data Analysesmentioning
confidence: 99%